Statistical Analysis of Physical Culture and Health in Poland - Artur GRABOWSKI (Communications of International Proceedings, 2025)
This study explores the economic and social impact of physical activity, focusing on its role in reducing public health costs and enhancing overall well-being. Recognizing physical activity as a valuable investment, the research analyzes the barriers to participation in sports and recreational activities among Polish households and assesses the consequences of inactivity. Using both qualitative and quantitative methods, including correlation and regression analysis, the study examines the relationship between household and public expenditure on physical culture and outcomes such as sick leave, treatment costs, and population health. Findings indicate that increased investment in physical activity—both at the individual and institutional level—can significantly contribute to improved health and reduced economic burdens associated with illness.
Keywords: public finance; physical activity; health; sports economics.